A qualitative study of the experiences of relatives to brought in dead persons in an emergency department. (17th August 2022) - Bove, Dorthe Gaby; Herling, Suzanne Forsyth; Sørensen, Nanna; Gjersøe, Peter; Timm, Helle
Abstract: Aims: The aim was to explore the experiences of relatives seeing and saying goodbye to brought in dead persons in a Danish emergency department. Design: This was a qualitative study based on interpretive description methodology. Methods: Data were collected through semi‐structured individual interviews with relatives ( n = 11) of brought in dead persons and 30 h of participatory observations of these relatives visiting the emergency department to see and say goodbye to the deceased. Data were collected between February 2019 and December 2020. Results: Our analyses revealed internal and external chaos as an overarching theme, covering 4 themes and 10 subthemes. The four themes were traumatic events, restricted access, briefly being together again, and final goodbyes and departures. Conclusion: Emergency departments were highly acute and busy settings that prioritized survival more than the care of deceased people and their relatives. The relatives were, in every way, affected by internal and external chaos; the external chaos in the emergency department reinforced the feeling of internal chaos. It is necessary for managers and nurses in emergency departments to organize and practice care for relatives, whilst bringing in deceased individuals in a less chaotic and more caring manner. Impact: This study contributes to the knowledge of relatives' experiences regarding brought in dead persons, underpinning the need to care for this subpopulation in emergency departments. Care for relatives of brought in dead individuals has the potential to relieve suffering and prevent diseases, which are core elements of nursing.